2021
DOI: 10.3390/brainsci11101273
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiological Basis of Cognitive Side Effects of Electroconvulsive Therapy: A Systematic Review

Abstract: Decades of research have consistently demonstrated the efficacy of electroconvulsive therapy (ECT) for the treatment of major depressive disorder (MDD), but its clinical use remains somewhat restricted because of its cognitive side effects. The aim of this systematic review is to comprehensively summarize current evidence assessing potential biomarkers of ECT-related cognitive side effects. Based on our systematic search of human studies indexed in PubMed, Scopus, and Web of Knowledge, a total of 29 studies ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Recent studies have found potential roles of oxidative stress, inflammation, neurotrophic factors, immunological factors, hormones, alterations in electrical brain activity, permeability of the blood brain barrier, brain perfusion, changes in functional networks with a lag of integration of new neurons and volume changes of the hippocampus. 9 , 84 , 85 Further study of the worthwhile pharmacological interventions in this review may help elucidate the mechanisms of cognitive side effects in ECT. In addition, the study of novel candidates may contribute to further understanding of these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found potential roles of oxidative stress, inflammation, neurotrophic factors, immunological factors, hormones, alterations in electrical brain activity, permeability of the blood brain barrier, brain perfusion, changes in functional networks with a lag of integration of new neurons and volume changes of the hippocampus. 9 , 84 , 85 Further study of the worthwhile pharmacological interventions in this review may help elucidate the mechanisms of cognitive side effects in ECT. In addition, the study of novel candidates may contribute to further understanding of these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that industry-funded sponsorship might discourage the publication of unfavourable results. Furthermore, evidence has shown that papers funded by independent organisations have generated fewer positive findings than those conducted by industry-funded sponsors (Bekelman 2003).…”
Section: The Review's Methodsmentioning
confidence: 99%
“…ECT is shown to increase the volume and enhance connectivity of the temporal lobe cortices, anterior cingulate cortex and hippocampus, resulting in favourable clinical outcomes which are believed to be due to neuroplastic changes (Ota 2015;Joshi 2016;Cano 2017). However, the increase in hippocampal volume is associated with cognitive adverse effects, which evidence suggests improve as hippocampal volume decreases in the 6-12 months following completion of ECT (Bassa 2021). MST, in contrast, induces only superficial stimulation and passes through the skull unimpeded, resulting in a more targeted stimulation of focal structures (Weissman 2020).…”
Section: Ect and Mstthe Proposed Mechanism Of Actionmentioning
confidence: 99%
“…However, a recent systematic review and meta-analysis only identified a younger age as factor related to cognitive deterioration after the ECT-course ( 5 ). The literature reports several pathophysiological theories regarding negative cognitive ECT-outcome, including changes in neuroinflammation, neurotrophic factors, and hormones ( 9 ). Magnetic resonance imaging (MRI) studies have shown an increase in hippocampal volume associated with increased cognitive disturbances ( 5 ).…”
Section: Introductionmentioning
confidence: 99%